EGG ROLL FORMULATION FROM PURPLE-YELLOW AND WHITE SWEET POTATOES (Ipomoea Batatas L) WITH SOYBEANS (Glycine Max Merill) SUBTITUTE - Pradita, Nanda; Widanti, Yannie Asrie; Wulandari, Yustina Wuri (JITIPARI (Jurnal Ilmiah Teknologi dan Industri Pangan UNISRI), 2021)
Egg roll is a snack that tastes sweet and tasty, crunchy, in the form of a long roll with a hole, a distinctive aroma that comes from the many combinations of ingredients used, processed by baking. Soybeans are used as raw material because they are quite economical, have high nutritional value, such as protein, vitamins, minerals and the best fiber. Sweet potato contains nutrients that have a positive effect on health, a good source of carbohydrates, has the potential for a fairly wide use and is suitable for food diversification programs, which are expected to reduce dependence on wheat flour. The research objective is to determine the right egg roll formulation between the ratio of sweet potato flour and soybeans so that a high protein product is produced and the highest value is obtained for the overall preference, determine the nutritional content contained in the egg roll and determine the quality of the sweet potato egg roll which includes bright colors. , visible flavor and crunchy texture. The results of this study indicate that the best yellow and white egg roll formulation of soybean substitution based on the treatment of 60% sweet potato flour: 40% soybeans with a moisture content of 5.01%, an ash content of 2.62%, a protein content of 11.63%, fat content 14.47%, bright color and crunchy texture.